Cardiovascular disease in familial hypercholesterolaemia: Influence of low-density lipoprotein receptor mutation type and classic risk factors - Alonso, R.; Mata, N.; Castillo, S.; Fuentes, F.; Saenz, P.; Muñiz, O.; Galiana, J.; Figueras, R.; Diaz, J.L.; Gomez-Enterría, P.; Mauri, M.; Piedecausa, M.; et al. (Atherosclerosis, 2008)
To determine the effect of the type of mutation in low-density lipoprotein receptor gene and the risk factors associated with the development of premature cardiovascular disease (PCVD) in a large cohort of heterozygous familial hypercholesterolemia (hFH) subjects with genetic diagnosis in Spain. A cross-sectional study was conducted on 811 non-related FH patients (mean age 47.1 ± 14 years, 383 males and 428 females) with a molecular defect in the low-density lipoprotein receptor ( LDLR) gene from the Spanish National FH Register. Prevalence of PCVD was 21.9% (30.2% in males and 14.5% in women, P < 0.001). Mean age of onset of cardiovascular event was 42.1 years in males and 50.8 years in females. Of those patients with PCVD, 59.5% of males and 27% of females suffered a second cardiovascular (CV) event. In multivariate analysis male gender, age, tobacco consumption (ever), and total cholesterol/HDL-cholesterol (TC/HDL-C) ratio were significantly associated with PCVD. Two hundred and twenty different mutations were found with a large heterogeneity. Patients carrying null-mutations had significantly higher frequency of PCVD and recurrence of CV events. No relationship with Lp(a) levels and genotype of Apo E were found. This study confirms the importance of identifying some classic risk factors such as smoking and TC/HDL-C ratio, and also the type of mutation in LDLR gene in order to implement early detection and intensive treatment for the prevention of cardiovascular disease in FH patients.